WHOLE BODY VIBRATION TRAINING IMPROVES MUSCULAR POWER IN A RECREATIONALLY ACTIVE POPULATION - Adam Hawkey (University of Banja Luka, Faculty of physical education and sport, 2012)
Whole body vibration training improves muscularpower in a recreationally active population